Latest development in salt removal from solar-driven interfacial saline water evaporators: Advanced strategies and challenges. (15th June 2020) - Li, Haoran; Yan, Zhe; Li, Yan; Hong, Wenpeng
Abstract: Solar-driven interfacial water evaporation, which gets rid of the limitation of saline waters, enables to supply potable water in the worldwide, especially in remote areas where only solar energy and water are available. This technique has also exhibited great potential applications in fields such as seawater desalination, steam sterilization, and fuel production. However, the evaporation efficiency decreases during continuous operation in saline water due to the blockage of the solar absorber resulting from crystalline salt deposition. Therefore, it is still a great challenge to design a stable and efficient solar-driven interfacial saline water evaporator. Herein, a variety of structural designs and engineering strategies for salt removal of evaporators in the latest years were reviewed. We classified these strategies as remaining unsaturated evaporation of saline water, preventing salt ions from contacting the solar absorber, dissolving and/or migrating back of crystalline salts, and keeping salt crystallization away from evaporation area. Finally, the current challenges and future research opportunities were discussed. The purpose of this review was: (1) to provide ideas to solve the problem of the reduced efficiency causing by salt deposition during saline water evaporation and (2) to promote the application of solar-driven interfacial saline water evaporation technology by providing the latest achievements in structural designs for salt removal. Graphical abstract: Image 1 Highlights: The progress of solar-driven interfacial saline water evaporation was highlighted. The potential application of interfacial saline water evaporation was pointed out. The advanced design concepts for salt removal were reviewed and discussed. The current challenges and future research opportunities were emphasized.